CARBON ISOTOPE EFFECTS IN CARBONATE SYSTEMS - Deines P. (My University, 2004)
Global carbon cycle models require a complete understanding of the δ13 C variability of the Earth’s C reservoirs as well as the C isotope effects in the transfer of the element among them. An assessment of δ13 C changes during CO2 loss from degassing magmas requires knowledge of the melt-CO2 carbon isotope fractionation. In order to examine the potential size of this effect for silicate melts of varying composition, 13C reduced partition functions were computed in the temperature range 275 to 4000 K for carbonates of varying bond strengths (Mg, Fe, Mn, Sr, Ba, Pb, Zn, Cd, Li, and Na) and the polymorphs of calcite. For a given cation and a given pressure the 13 C content increases with the density of the carbonate structure. For a given structure the tendency to concentrate 13 C increases with pressure.